The wealth effect of share buybacks: evidence from Malaysia - Chong, L. Y.; Md Nassir, Annuar; Mohd Ashhari, Zariyawati (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
This paper investigates stock market reactions surrounding the announcement of actual share buybacks by companies listed on the Main Market of Bursa Malaysia from 2007 through 2011. An event study methodology was used to examine stock price reactions to 100 announcements of share buybacks involving 100 different listed companies. The market-adjusted return model (MARM) was used to capture the abnormal returns as share buybacks mostly involved actively traded companies. Overall, the CAAR, which was used to measure the wealth effect, showed an uptrend, but was not statistically significant for about 12 days after the event day before stabilising. This showed a positive wealth effect arising from the announcement. Thus, one can weakly conclude that the market generally responded favourably to the announcement of share buybacks. The evidence tends to support the signalling hypothesis and is consistent with the under valuation hypothesis.